Perceptions and barriers to the use and training of point-of-care ultrasound among Finnish emergency physicians – a nationwide survey - Järvinen, Jesse; Hannula, Otso.; Meuronen, Anna; Mattila, Kalle (Springer Science and Business Media LLC, 2025)
Background
Point-of-Care Ultrasound (POCUS) has become integral to emergency medicine (EM) as a critical diagnostic support tool. In Finland, where EM was formally recognised as a specialty as recently as in 2013, a historical lack of systematic training for POCUS has existed. Such training has largely depended on individual initiative rather than a standardised program while many other areas of EM training have already seen the introduction of structured education. The aim of this study is to identify key factors and barriers influencing POCUS training, with the goal of improving its quality and delivery.
Methods
A nationwide survey was conducted among emergency physicians, trainees, and specialists across Finnish emergency departments from late 2020 to early 2021. The survey included detailed questions on POCUS training, perceived barriers to training, experiences of the successful initiation of more structured approaches, as well as attitudes towards the integration of POCUS into clinical practice. Statistical methods for quantitative data and thematic analysis for qualitative data were used.
Results
A total of 134 emergency physicians completed the survey, revealing a strong consensus among participants for several training needs. Key barriers identified include inadequate training, limited supervision, device availability, and time allocation. Notably, out of all open-ended questions, 96.5% of respondents called for the initiation of structured training programs that accommodate both foundational and advanced practitioner needs. Furthermore, hands-on training and senior support were highly valued.
Conclusions
The results highlight a need for reform in POCUS training in Finland, demonstrating a need for structured, competency-based educational frameworks that align with international standards. Improvements on training infrastructure, including enhanced mentorship and increased access to ultrasound equipment, are essential enablers of such a reform.